Spatial-temporal variations of natural disasters during the Ming & Qing Dynasties (1368–1912AD) in Chaohu Lake Basin, East China. (22nd February 2018) - Wu, Li; Zhou, Hui; Zhang, Shitao; Li, Linying; Zhang, Mengcui; Ji, Chao
Abstract: The Ming & Qing Dynasties experienced the Little Ice Age (LIA), a most abnormal climate event in nearly 2000 years' of Chinese history, in which various natural disasters took place frequently. On the basis of systematically collecting and collating historical documents related to natural disasters, and by adopting mathematical statistics, geological succession, correlation and other methods, analysis and comparison were made on the spatial-temporal differentiation of disasters and correlation between various major natural disasters taking place in the Chaohu Lake Basin during the Ming & Qing Dynasties (1368–1912AD). The results show that 753 major disasters took place in the Chaohu Lake Basin during the Ming & Qing Dynasties. Among these, floods and droughts accounted for the largest percentage, while other disasters occurred occasionally. The Little Ice Age (1550–1850AD) was the period with a high incidence of natural disasters, and in the years from 1701 to 1750 natural disasters took place most frequently; between 1651–1700AD there was a declining period of flood frequency, though there were historically high occurrences of droughts and earthquakes. There were more floods than droughts suffered by Hefei, Shucheng, Chaohu, Wuwei and Hexian, while more droughts than floods suffered by Hanshan and Lujiang. Earthquakes in the basin mainly occurred in Chaohu, Shucheng, Hexian and Hefei, which are all near the Tan-Lu Fracture. The opposite is true for changes in the time scale of floods and droughts; this was probably caused by intra-seasonal oscillations of the subtropical high. The correlation between hails and wind disasters is significant, while other disasters are weakly correlated. There exists a certain association between spatial differentiation of occurrence frequency of natural disasters and landforms in the basin. The disaster-prone environment features landforms including plains, hills, low mountains, and these have a significant impact on the spatial distribution of five major natural disasters in the Chaohu Lake Basin.